Analisis Vegetasi di Kawasan Petilasan Mbah Maridjan Taman Nasonal Gunung Merapi - Amri Shabirin; Yuliantika Puteri; Hendrianis Syafira; Tia Mayasari; Mufti Nurkhasanah (Biotropic : The Journal of Tropical Biology, 2020)
This research aims to determine the diversity of habitus and species that dominate in the region of Kinahrejo, Umbulharjo, Cangkringan, Sleman. The method used is square sampling by making a 7x7 meters square plot of 2 plots so that an area of ​​98 m2 is obtained. Vegetation analysis using the method of observation, and monitoring (field observation) directly with random sampling and using the principle of representative. Analysis the level of habitat diversity using the Shannon-wienner Index and determination of species that dominate using the calculation of the Important Value Index (INP). A total of 34 species consisting of mosses, shrubs, herbs, and stand-structure are occupy the observation area. The results of the research and analysis showed that Tamarindus indica, which included stand-structure habitus had the highest INP of 139.54% and the lowest INP was found in shrubs habitus. The highest Shannon-wienner index in shrubs habitus is 1.220928 and the lowest is in stand-structure habitus. It can be concluded, stand-structure habitus dominates the area while, the highest diversity is found in shurbs habitus. The eruption in 2010 caused damage to ecosystems and invasive plants to become dominant such as Acacia decurrens and shrubs.